Inhibition of Pertussis Toxin by Human α-Defensins-1 and -5: Differential Mechanisms of Action - Kling C; Sommer A; Almeida-Hernandez Y; Rodríguez A; Perez-Erviti JA; Bhadane R; Ständker L; Wiese S; Barth H; Pupo-Meriño M; Pulliainen AT; Sánchez-García E; et al. (Switzerland, 2025)
Whooping cough is a severe childhood disease, caused by the bacterium Bordetella pertussis, which releases pertussis toxin (PT) as a major virulence factor. Previously, we identified the human antimicrobial peptides α-defensin-1 and -5 as inhibitors of PT and demonstrated their capacity to inhibit the activity of the PT enzyme subunit PTS1. Here, the underlying mechanism of toxin inhibition was investigated in more detail, which is essential for developing the therapeutic potential of these peptides. Flow cytometry and immunocytochemistry revealed that α-defensin-5 strongly reduced PT binding to, and uptake into cells, whereas α-defensin-1 caused only a mild reduction. Conversely, α-defensin-1, but not α-defensin-5 was taken up into different cell lines and interacted with PTS1 inside cells, based on proximity ligation assay. In-silico modeling revealed specific interaction interfaces for α-defensin-1 with PTS1 and vice versa, unlike α-defensin-5. Dot blot experiments showed that α-defensin-1 binds to PTS1 and even stronger to its substrate protein Gαi in vitro. NADase activity of PTS1 in vitro was not inhibited by α-defensin-1 in the absence of Gαi. Taken together, these results suggest that α-defensin-1 inhibits PT mainly by inhibiting enzyme activity of PTS1, whereas α-defensin-5 mainly inhibits cellular uptake of PT. These findings will pave the way for optimization of α-defensins as novel therapeutics against whooping cough.